2016
DOI: 10.4172/2167-1044.1000229
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Obsessive Compulsive Symptoms among Patients with Bipolar-I Disorder

Abstract: Background: Clinicians have observed the occurrence of obsessive and/or compulsive symptoms within the course of bipolar disorder. However the pattern of their occurrence is not clearly delineated. This study aimed to explore this pattern.Method: A cross sectional study. All patients were assessed by the Structured Clinical Interview for DSM-IV (SCID I) to diagnose bipolar disorder (BD) and comorbid obsessive compulsive (OC) symptoms. The symptom severity was assessed by Young Mania Rating Scale (YMRS), Beck D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This study employed a cross sectional study on selected patients to diagnose bipolar disorder (BD) and comorbid obsessive compulsive (OC) symptoms. Investigations of the study found that underlined symptoms were observed in case of unemployment, greater functional impairment, and less smoking and most common obsessions were contamination, religious and aggressive obsessions, cleaning and counting compulsions [1].…”
Section: Editor's Notementioning
confidence: 91%
“…This study employed a cross sectional study on selected patients to diagnose bipolar disorder (BD) and comorbid obsessive compulsive (OC) symptoms. Investigations of the study found that underlined symptoms were observed in case of unemployment, greater functional impairment, and less smoking and most common obsessions were contamination, religious and aggressive obsessions, cleaning and counting compulsions [1].…”
Section: Editor's Notementioning
confidence: 91%